NOTIONAL AND FUNCTIONAL WORDS: UNDERSTANDING THEIR ROLE IN LANGUAGE - Nasridinova Xumorabonu Usen qizi; Astanova Dilafruz Murodovna (PEDAGOGS, 2024)
Language is a complex system of communication that comprises various components, including words classified into different categories based on their functions and meanings. Among these categories, notional and functional words play crucial roles in constructing meaningful sentences. Notional words convey specific meanings and concepts, while functional words serve grammatical purposes, helping to structure sentences and clarify relationships between ideas. This article explores the definitions, characteristics, and roles of notional and functional words in language, illustrating their significance with examples and discussing their implications for language learning and teaching.